Temporal video quality assessment method involving structural similarity index - Loh, Woei-Tan; Bong, David B.L. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper, a video quality assessment (VQA) that focuses on temporal part is being proposed. It is based on Structural Similarity Index (SSIM) and the work of previous researchers where differences of the frames are being measured. The proposed VQA possesses lower computational complexity and acceptable performance compared to state-of-the-art VQA methods.